Inventarisasi Jenis-Jenis Tumbuhan Berkhasiat Obat di Hutan Hujan Dataran Rendah Desa Nyamplung Pulau Karimunjawa - Muhammad Abdullah; Dewi Mustikaningtyas; Talitha Widiatningrum (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2010)
The research aims to obtain information about the various of medicinal plantsspecies. from 17 species of wild plants were found, approximately 76.5% (13)has been known to have the potential to be used as a medicine, namely jambumete, kecapi, gondang putih, laban, petai cina, jati, gerok ayam, lampeni, jemang,mangga, beruas, karet manis, and kopi anjing.Keywords: medicinal plant, lowland rain forest, Karimunjawa